Penerapan Model Pembelajaran Inquiry Learning Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Pada Materi Fluida Statis Di Kelas XI 2 SMA Negeri 3 Padangsidimpuan - Nasri Adlani Lubis; Herti Vioni; Yenni Khairani Lubis (Institut Agama Islam Negeri Padangsidimpuan, 2026)
This research is motivated by the low critical thinking skills of students in Physics in grade XI 2 students of SMA Negeri 3 Padangsidimpuan. This low critical thinking skills are evident in their lack of active participation in the learning process and their low learning outcomes, which have not yet reached the Learning Objective Achievement Criteria (KKTP). This study aims to determine the inquiry learning model to improve students' critical thinking skills in static fluids in grade XI 2 students of SMA Negeri 3 Padangsidimpuan. The type of research used is Classroom Action Research (CAR) with the Kurt Lewin model, which consists of planning, action, observation, and reflection. The study was conducted in two cycles with 33 students as subjects. Data collection techniques used teacher and student observations (cycle I meeting 1 (teacher 73% and student 54%), cycle I meeting 2 (teacher 80% and student 64%), cycle II meeting 1 (teacher 86% and student 74%) and cycle II meeting 2 (teacher 100% and student 80%). and student critical thinking skills tests cycle I meeting 1 (average score 68.7 and completeness 39%), cycle I meeting 2 (average score 73.2 and completeness 42%), cycle II meeting 1 (average score 78.1 and completeness 60%) and cycle II meeting 2 (average score 83.6 and completeness 78%), until reaching 78% in cycle II. Thus, the application of the Inquiry Learning learning model is effective in improving students' critical thinking skills on static fluid material in class XI 2 SMA Negeri 3 Padangsidimpuan.